Resources Estimation of Laterite Nickel Using Ordinary Kriging Method at PT Mahkota Semesta Nikelindo District Wita Pond Morowali District - Nawir, Alfian; Thamsi, Alam Budiman; Sanjaya, Harta; Aswadi, Muhammad (Universitas Sanata Dharma, 2023)
Resources have economic value, form, quality, quantity, grade, geological characteristics and certain sustainability to be extracted economically. Mineral resources decrease based on the level of geological confidence into the Inferred, Indicated and Measured category. This study aims to assess the potential of nickel laterite resources and the distribution of nickel mineralization levels in the study area using the Ordinary Kriging geostatistical method. The research methodology was inspired by statistical and geostatistical analysis, starting with univariant statistical analysis, spatial statistics, bivariant statistics and resource estimation. for later use in determining the distribution of mineralization grades and classifying nickel laterite resources using the RKDS (Relative Kriging Standard Deviation) calculation. This method is used to estimate nickel content in a block whose grade value is unknown. The results of statistical calculations using Ordinary kriging obtained an average grade value of 2.90% Ni. Mineralization data for nickel content in limonite layers with Ni content of 0.5 – 1.3% and in saprolite layers with Cut of Grade (COG) Ni, 1.4 – 3.1% Ni in limonite and saprolite layers are projected in the block model. The estimated tonnage of nickel resources using the OK method is 670,837.83 tonnes. The results of laterite nickel resource classification using the RKSD (Relative Kriging Standard Deviation) calculation are classified into measured resources (Measured).